Cardiovascular and selected comorbidities in early arthritis and early spondyloarthritis, a comparative study: results from the ESPOIR and DESIR cohorts. Issue 1 (14th September 2015) - Gherghe, Ana Maria; Dougados, Maxime; Combe, Bernard; Landewé, Robert; Mihai, Carina; Berenbaum, Francis; Mariette, Xavier; Wolterbeek, Ron; van der Heijde, Désirée
Abstract : Objectives: To investigate the prevalence of comorbidities in early rheumatoid arthritis (ERA) and early axial spondyloarthritis (ESpA) versus the general population. Methods: Baseline data of 689 patients with ERA from the Etude et Suivi des Polyarthrites Indifférenciées Récentes (ESPOIR) cohort (age 48.2±12.1 years, symptoms duration 14.2±14.5 weeks) and 645 patients with ESpA from Devenir des Spondylarthropathies Indifférenciées Récentes (DESIR; age 32.8±8.4 years, axial symptoms duration 79.0±45.7 weeks) were analysed. Metabolic and cardiovascular diseases (CVD), infections and neoplasia were determined in each cohort. The prevalence (95% CI) of several comorbidities was compared with that in the French general population. For patients without CVD, the 10-year risk of developing CVD was calculated using the Framingham and SCORE equations. The heart age was calculated using the 2008 Framingham points system. Results: 42% of patients with ERA and 20.3% of patients with ESpA had at least 1 comorbidity; the most common were arterial hypertension (AHT) and dyslipidaemia. AHT prevalence (95% CI) in ERA (18.2% (15.5% to 21.3%)), but not in ESpA (5.08% (3.57% to 7.14%)), was significantly increased (p<0.05) compared with the general population (7.58%). Prevalence of tuberculosis history was higher in ERA (4.7% (3.3% to 6.6%)), and ESpA (0.99% (0.4% to 2.3%)) than in the general population (0.02%; both p<0.05). No differences were observed in malignancies, coronary heart disease or diabetes. In ERA, among patients without a history of CVD, an intermediate to high CVD risk was found. The heart age exceeded the real age by 4.1±9.6 years in ERA and by 2.1±7.0 years in ESpA (p<0.001). Conclusions: We found an increased prevalence of AHT and tuberculosis history in ERA and ESpA, and an increased CVD risk. These results should prompt rheumatologists to check these comorbidities early in the disease.